Diagnostic value of lactate, procalcitonin, ferritin, serum-C-reactive protein, and other biomarkers in bacterial and viral meningitis: A cross-sectional study. Issue 35 (September 2017) - Sanaei Dashti, Anahita; Alizadeh, Shekoofan; Karimi, Abdullah; Khalifeh, Masoomeh; Shoja, Seyed Abdolmajid
Abstract : Abstract: There are many difficulties distinguishing bacterial from viral meningitis that could be reasonably solved using biomarkers. The aim of this study was to evaluate lactate, procalcitonin (PCT), ferritin, serum-CRP (C-reactive protein), and other known biomarkers in differentiating bacterial meningitis from viral meningitis in children. All children aged 28 days to 14 years with suspected meningitis who were admitted to Mofid Children's Hospital, Tehran, between October 2012 and November 2013, were enrolled in this prospective cross-sectional study. Children were divided into 2 groups of bacterial and viral meningitis, based on the results of cerebrospinal fluid (CSF) culture, polymerase chain reaction, and cytochemical profile. Diagnostic values of CSF parameters (ferritin, PCT, absolute neutrophil count [ANC], white blood cell count, and lactate) and serum parameters (PCT, ferritin, CRP, and erythrocyte sedimentation rate [ESR]) were evaluated. Among 50 patients with meningitis, 12 were diagnosed with bacterial meningitis. Concentrations of all markers were significantly different between bacterial and viral meningitis, except for serum ( P = .389) and CSF ( P = .136) PCT. The best rates of area under the receiver operating characteristic (ROC) curve (AUC) were achieved by lactate (AUC = 0.923) and serum-CRP (AUC = 0.889). The best negative predictive values (NPV) for bacterial meningitis were attained by ANC (100%) and lactate (97.1%). The results of our study suggest that ferritin and PCT are not strong predictive biomarkers. A combination of low CSF lactate, ANC, ESR, and serum-CRP could reasonably rule out the bacterial meningitis.